PELAKSANAAN PELAYANAN PEMBUATAN ELEKTRONIK KARTU TANDA PENDUDUK (E-KTP) PADA KANTOR UNIT PELAKSANA TEKNIS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KANTOR KECAMATAN BONAI KABUPATEN ROKAN HULU TAHUN 2014 - Yulfianti "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Republic of Indonesia is a democratic United Nation.Democracy is government system from people by the people and for the people.One of implementation of democracy in Indonesia at this moment is by giving right and autonomous authority from the central government to the regional government.In this case,implementation of Government’s programs can be reached successfully by Regional Government.In accelerating in reaching out all the purposes,our government implemented E_Government .The purpose of this program is how to realize democratic ,transparent,fair, accountable, responsible, responsive, efficient and effective government. One of realization of the program is by implementing Electronic_Identity Card. Based on data from 2011 – 2014 at Departement of Population and Civil Registration Rokan Hulu Regency,Sub_District Unit Office Bonai,researcher found many problems about Electronic_Identity Card Service.The problems were about distribution forms of Electronic_Identity Card,the number of operators was not enough yet,electrical supplies,socialization,limited facilities and budgeting for buying generator.The problems influenced quality service for people in getting the Electronic_Identity Card. This research used qualitative method.In solving the problems is that the central and regional government have to cooperate in preparing facilities for giving the best service for people who wants to get the Electronic_Identity Card at Departement of Population and Civil Registration Rokan Hulu Regency,Sub_District Unit Office Bonai.Keywords : Implementation, government, demoracy